PERSEPSI MASYARAKAT TERHADAP DAMPAK KESEHATAN DARI AKTIVITAS PENAMBANGAN BATUBARA DI KAMPUNG TASUK KABUPATEN BERAU - Musyidin Mursyidin; Husnul Warnida (Jurnal Ilmiah Manuntung, 2016)
Mining is an ancient occupation, long recognized as being arduous and liable to injury and disease. Coal mining carried dangers from exposure to noise, heat, and airborne dusts, causing many associated diseases. Respiratory diseases caused by coal mine dust are pneumoconiosis, chronic bronchitis, and emphysema. The process of coal mining involves the discharge of huge amount of effluent into the surface water. Effluent from coal mine contains high load of TSS, TDS, calcium carbonate and heavy metals accumulates in water, soil, sediment and living organism. Coal mining has long been established in East Kalimantan. This paper explores the public perceptions of the health and environmental impact of opencast coal mining in Kampung Tasuk, Gunung Tabur, Regency of Berau, East Kalimantan. The obtained result may be used as an input to formulate and redesign the community development program of coal mining company in Berau. The public perception of coal mining activity in kampung Tasuk was dissastified with costumer satisfaction index 58.1